Carbon Nanostructures: Covalently Connected Carbon Nanostructures for Current Collectors in Both the Cathode and Anode of Li–S Batteries (Adv. Mater. 41/2016). Issue 41 (November 2016) - Jin, Song; Xin, Sen; Wang, Linjun; Du, Zhenzhen; Cao, Lina; Chen, Jiafeng; Kong, Xianghua; Gong, Ming; Lu, Junling; Zhu, Yanwu; Ji, Hengxing; Ruoff, Rodney S.
Abstract : On page 9094, a 3D current collector made of carbon‐nanotube forests, covalently connected to an ultrathin graphite foam by carbon–carbon bonds is described by H. X. Ji and co‐workers. The 3D current collector renders a high‐rate capacity of 860 mA h g −1 at 12 C for a Li–S cell assembled using these current collectors, with the cathode loaded with elemental sulfur and the anode loaded with lithium metal.